Tolerant Religious Guidance Practices at the Maiyah Mocopat Syafa’at Recitation in Yogyakarta - K., Sulfikar; Sabaruddin, Sabaruddin (Program Studi Bimbingan dan Konseling Islam, 2025)
The issue of religious intolerance in Indonesia remains high and threatens social cohesion. Tolerant religious guidance is crucial for maintaining harmony. The Maiyah Mocopat Syafa’at Religious Study Forum serves as an inclusive space emphasizing dialogue, openness, and humanitarian values. This study examines the practice of tolerant religious guidance in a socio-cultural context. This study aims to understand the practice of tolerant religious guidance at the Maiyah Mocopat Syafa’at Religious Study Forum in Yogyakarta. Using a qualitative approach, data were obtained through observation, in-depth interviews, and documentation. The results show that religious guidance in this forum is participatory, non-hierarchical, and culturally based. The Maiyah Forum does not differentiate between preachers and congregants, but rather builds a space for open, equal dialogue. Guidance materials are contextual and reflective, and are delivered through the medium of art and culture. Values ​​of tolerance such as equality, openness to differences, and empathy are the foundation of religious practice in this forum. In addition, Maiyah serves as an alternative religious literacy space, a forum for interfaith and cultural dialogue, and a vehicle for fostering humanistic spirituality. These findings indicate that the inclusive culture and spirituality-based religious guidance approach in Maiyah is able to foster moderate, open, and peaceful religious attitudes.